Pengaruh Good Corporate Governance Terhadap Pengungkapan Islamic Social Reporting - Mike Sonita Sari; Nayang Helmayunita (Jurnal Eksplorasi Akuntansi, 2019)
Sharia issuers are determined by considering Islamic principles and it is expected that company activities will be in harmony with Islamic law and framework. ISR is part of corporate social responsibility that should be disclosed by Islamic issuers. However, ISR disclosure is still voluntary, so the level of disclosure of each sharia issuer still varies. This study aims to examine the effect of Good Corporate Governance (GCG) on disclosure of Islamic Social Reporting (ISR). The total samples used in this study is 65 annual reports from 13 companies registered in the Jakarta Islamic Index (JII) for the period 2013-2017. The measurement of ISR disclosure is done by means of content analysis through scoring methods on the annual reports of each sharia issuer. Data analysis was performed with descriptive statistics and classic assumption tests and hypothesis testing with multiple linear regression, F test, R2 test, and t test. The results showed that the frequency of board of commissioner meetings had a significant positive effect on ISR disclosure. The size of independent commissioners, the size of the audit committee, and public ownership have a significant negative effect on ISR disclosure. Institutional ownership and managerial ownership have no effect on ISR disclosure.